Few-Shot Cold-Start Workload Forecasting for New AI Inference Tenants with Time-Series Foundation Models - Shilu He; Chengliang Li; Hengning Rao (University of Science and Computer Technology, 2025)
This paper presents a reproducible empirical study of few-shot cold-start workload forecasting for new AI inference tenants using the Alibaba GPU-disaggregated DLRM serving trace. Instance lifecycles are transformed into hourly active-demand series, and resource reservations are normalized into capacity units to evaluate 24-hour forecasting under zero-shot, 5-shot, 10-shot, and full-history settings. Seven forecasting methods are compared: archetype mean prior, persistence, moving average, linear trend, seasonal naive, global residual ridge, and CT-TSFM, a compact cross-tenant time-series foundation model. The cold-start evaluation uses 46 held-out tenants, with 110 source tenants for pretraining and calibration. Results show that hourly demand is strongly persistence-dominated. Zero-shot forecasting yields a mean absolute error (MAE) of 326.26 normalized capacity units, whereas only five observations reduce MAE to 4.00 for persistence, global residual ridge, and CT-TSFM. Validation consistently selects a residual gate of 0.0 for CT-TSFM, indicating that retaining the persistence prior and rejecting cross-tenant residual transfer is the most reliable strategy. Calibration intervals achieve approximately 85–87% coverage against a 90% target. The findings demonstrate that a few recent observations substantially improve cold-start forecasting, while source-tenant metadata alone provides limited zero-shot planning capability.